Hubungan Usia, Tingkat Pendidikan dan Tingkat Pengetahuan terhadap Cara Penggunaan Metered Dose Inhaler (MDI) pada Pasien Asma di RSUD Dr. Moewardi - Kusumawardhany, Fitria Marizka; Setijadi, Ana Rima; Primadewi, Novi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Asthma is a chronic airway inflammatory disease that seriously impact on morbidity and mortality in the world. Most of the patients were taking medication prescribed for inhalation using a tool, not using inhalation devices correctly, approximately 90% of patients showed a wrong way to use MDI.Â For that, need to be investigated the factors associated with the occurrence of errors how to use MDI.Â This study aimed to analyze the relationship between age, education level and level of knowledge on how to use MDI in asthma patients. Methods: This analytic study was observational with cross-sectional approach. A sample of 40 study subjects was selected by purposive sampling from out asthma patients visiting the Pulmonary Clinics, RSUD Dr. Moewardi Surakarta. The data were collected by interview using suggested checklist and a set of questionnaire. The data was analyszed using chi-square and multiple logistic regression model on SPSS version 17 for Windows. Results: Patients aged â¥ 65 years had a good way of using MDI 4/10 times lower than patients aged <65 years (OR = 0.43; CI 95% 0. 0.07 to 2.89; p = 0.388). Patients with high education level have a good way of using MDI 2 times higher than patients with low education level (OR = 1.68; CI 95% 0.32 to 8.82; p = 0.539). Patients with a high level of knowledge of the importance of how to use the correct MDI had a good way of using MDI 14 times higher than patients with low levels of knowledge (OR = 13.58; CI 95% 2.37 to 77.76; p = 0.003).This estimate has controlled for the effects of long use of MDI as a confounding variable. Conclusions: There is a statistically significant association between knowledge on how to use MDI. There are also the association between age and education level on how to use MDI in asthma patients even though the data obtained was not statistically significant. This conclusion is drawn after controlling for the effects of long use of MDI as a confounding variable. Keywords: Asthma, how to use MDI, age, education, knowledge Â